Calciphylaxis of the temporal artery masquerading as temporal arteritis: a case presentation and review of the literature. Issue 11 (November 2015) - Roverano, Susana; Ortiz, Alberto; Henares, Eduardo; Eletti, Mónica; Paira, Sergio
Abstract An 82-year-old woman came to consultation with sudden visual loss in her left eye. Fifteen days before, she complained of diplopia. She had doubtful symptoms of giant cell arteritis and showed a normal physical exam. Lab results showed erythrosedimentation rate (ESR) = 62 mm/1°h; uremia = 0.56 g/dl (normal <0.45); serum creatinine = 1.7 mg% (normal <1.4); low calcium and phosphorus; and normal urine calcium and serous PTH. Fundus exam and brain magnetic resonance imaging (MRI) showed normality of optic nerves, chiasma, retrochiasmatic area, ocular muscles, eyeballs, lacrimal glands, periorbital fat, cavernous sinuses, and occipital cortex. A temporal arteritis was suspected; therefore, a biopsy was carried on. It showed the presence of large calcium deposits in the artery's tunica media and internal elastic lamina, with narrowing of the lumen, with no inflammation and multinuclear giant cells. Histological diagnosis is calciphylaxis. Although calciphylaxis is a well-described entity that occurs in end-stage renal patients, many cases are due to non-uremic causes. To date, there are only six cases described in literature of calciphylaxis mimicking GCA.